Autopsies are indispensable in the advancement of patient care: Report of an unusual presentation and fatal outcome of an autopsy-diagnosed case of advanced idiopathic interstitial pneumonia - Evi Abada; Kunil Raval (Lung India, 2020)
Idiopathic interstitial pneumonias (IIPs) are a group of fibrosing lung disorders conferring significant morbidity and mortality to patients. Most patients with IIP first present with dyspnea and/or cough. Here, we report the case of a 53-year-old male who presented with severe abdominal pain and weight loss of approximately 100 pounds of 3-month duration. Symptoms of mild dyspnea and cough were obtained during additional history taking. Physical examination and computed tomography of the chest were suggestive of pneumonia, and he was placed on multiple antibiotics but developed worsening respiration that necessitated hyperbaric oxygen and died after 10 days. Histopathological examination of autopsy lung specimen, revealed severe lung damage secondary to a mixed IIP pattern of diffuse alveolar damage, superimposed on extensive interstitial fibrosis, with features of honeycombing, consistent with advanced interstitial/end-stage lung disease. This case typifies an unusual and fatal presentation of IIP, which may be useful in clinical practice.